2016
DOI: 10.1017/s1092852916000699
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes in infants exposed in utero to antipsychotics: a systematic review of published data

Abstract: The proportion of pregnancies exposed to either second-generation antipsychotics (SGAs) or first-generation antipsychotics (FGAs) varies between 0.3%-2% of all pregnancies, but, until now, little is known about the potential neurobehavioral teratogenicity of antipsychotics. Assessing this safety facet is the aim of this article. PubMed, Scopus, and Google Scholar were searched for eligible articles. PubMed (1954 to May 2016) was searched using several medical subject headings, variously combined. PubMed search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
0
14
1
1
Order By: Relevance
“…6 The risks of congenital anomalies and short-term neonatal complications associated with antipsychotic exposure in utero have been evaluated in epidemiologic studies, [7][8][9] however, data on the risk of neurodevelopmental disorders during childhood are sparse. [10][11][12][13] This is despite potential neurotoxic effects of some antipsychotics in vitro and in vivo, 14 and evidence that these substances cross the placenta. 15 Two recent systematic reviews 11 12 concluded that there was no clear evidence of longterm effects after exposure to antipsychotics in utero.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…6 The risks of congenital anomalies and short-term neonatal complications associated with antipsychotic exposure in utero have been evaluated in epidemiologic studies, [7][8][9] however, data on the risk of neurodevelopmental disorders during childhood are sparse. [10][11][12][13] This is despite potential neurotoxic effects of some antipsychotics in vitro and in vivo, 14 and evidence that these substances cross the placenta. 15 Two recent systematic reviews 11 12 concluded that there was no clear evidence of longterm effects after exposure to antipsychotics in utero.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…The effects of antidepressants and antipsychotics on infant development are yet to be reported. 18,19 For these reasons, continuous measurement of HC and developmental assessments are important in nonopioid NAS infants to reveal any associations. Further follow-up studies are needed since follow-up data were not obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference between the two groups for cognitive, language, motor, social, and emotional at 2, 6, and 12 months of age (Shao et al, 2015). Gentile and Fusco (2017) searched the English literature for neurodevelopmental studies in children exposed in utero to second generation antipsychotic drugs between1954 and 2016, and found mainly case reports and small case series. They performed a meta-analysis, on long-term outcomes of 35 healthy infants exposed in utero to antipsychotics.…”
Section: Neonatal Adaptation Difficultiesmentioning
confidence: 99%
“…They performed a meta‐analysis, on long‐term outcomes of 35 healthy infants exposed in utero to antipsychotics. Of these cases, three had motor developmental delays and one had delayed speech acquisition (Gentile and Fusco, ).…”
Section: Antipsychotic (Neuroleptic) Drugsmentioning
confidence: 99%